An intriguing "reversible reaction" in the fragmentation of deprotonated dicamba and benzoic acid in a Q‐orbitrap mass spectrometer: Loss and addition of carbon dioxide. (27th August 2020) - Chai, Yunfeng; Chen, Hongping; Lu, Chengyin
Abstract : Rationale: Loss of carbon dioxide is an important characteristic fragmentation reaction of deprotonated benzoic acid and its derivatives in electrospray ionization mass spectrometry. However, researchers have rarely noticed or believed that the loss of carbon dioxide in multistage mass spectrometry is a "reversible reaction, " that is, the fragment anion generated by carbon dioxide loss can capture another carbon dioxide to regenerate its precursor ion. Methods: The fragmentation of the [M − H] − ions of dicamba (3, 6‐dichloro‐2‐methoxybenzoic acid) and benzoic acid was performed with an electrospray ionization hybrid quadrupole‐orbitrap mass spectrometer. The structural confirmation of the precursor ions and their product ions was supported by accurate mass (elemental composition) analysis. Pseudo‐MS 3 experiments (in‐source collision‐induced dissociation as MS 2 ) and isotope labelling experiments were used to confirm the addition of carbon dioxide to the product ions in MS 2 . Results: In the fragmentation of deprotonated dicamba ( m / z 219), the relative abundance of the precursor ion does not decrease significantly or even increases as the collision energy increases. When the m / z 145 and 175 product ions were isolated in the mass analyzer, the ions 44 m / z units larger ( m / z 189 and 219) were generated spontaneously, indicating the formation of carbon dioxide adduct ions. In the fragmentation of deprotonated [ carboxyl ‐ 13 C]‐benzoic acid ( m / z 122), a deprotonated [ carboxyl ‐ 12 C]‐benzoic acid ion ( m / z 121) was generated which was derived from 13 CO2 loss and 12 CO2 addition. The isotope labelling experiment further supports the formation of CO2 ‐attached ions in the fragmentation of deprotonated benzoic acids. Conclusions: Under collisional activation, deprotonated dicamba and benzoic acids easily undergo carbon dioxide loss, but the decarboxylated product anions have an appropriate nucleophilicity to carbon dioxide and they can capture a background carbon dioxide molecule remaining in the vacuum system to regenerate the precursor ions. This study provides a new and deeper understanding of the gas‐phase chemistry of deprotonated benzoic acid derivatives in mass spectrometry.